The effect of combining surgical or endoscopic bariatric interventions with anti-obesity medication or probiotics on weight loss: a narrative review - de Waal, J. R.; Nieuwdorp, M.; Gerdes, V. E. A. (Frontiers in Endocrinology, 2026)
Obesity is a multifactorial chronic disease associated with multiple health complications. While bariatric surgery and endoscopic sleeve gastroplasty (ESG) are effective treatments for severe obesity, patients may still experience challenges such as weight regain or inadequate weight loss. As a result, combining these interventions with adjunctive treatment such as anti-obesity medication (AOM) or probiotics has become an area of increasing clinical interest. This narrative review summarizes the current evidence on the effect of combining surgical or endoscopic bariatric interventions with AOM or probiotics. Available studies suggest that the combination of GLP-1 receptor agonists (GLP-1 RA) and ESG leads to more weight loss than ESG alone. In contrast, non-GLP-1 RA medication show less consistent benefits and generally lower weight loss. GLP-1 RAs and tirzepatide show clinically relevant short term weight loss in patients with weight regain or insufficient weight loss after bariatric surgery. Other AOM, such as topiramate, phentermine, orlistat and bupropion/naltrexone result in more modest and variable outcomes. Relatively small studies on probiotics and prebiotics in combination with bariatric surgery do not find a statistically significant difference in weight loss between probiotic and placebo groups. Although small benefits in waist circumference, liver enzymes and vitamin uptake are mentioned, the effects are modest and not consistent across studies. In conclusion, combining AOM, especially GLP-1 RAs, with surgical or endoscopic obesity treatments appears to enhance weight loss in patients with suboptimal outcomes. These findings support the use of AOM as an adjunct to bariatric procedures. In addition, additional adequately powered studies are needed to evaluate the role for probiotics in improving weight loss after bariatric surgery. Future research should focus on long-term outcomes, side effects, and identifying patient subgroups that may benefit most from combined therapy.